PENGARUH PEMBERIAN JUS MELON TERHADAP PENURUNAN HIPERTENSI PADA LANSIA DI DESA KETEGAN - Ratna Aminati, Fifi; Yuni Yastutik, Iryani (LPPM STIKES HUSADA JOMBANG, 2024)
Hypertension is still the biggest problem for health especially in elderly, because hypertension is more experienced by the elderly than with teenagers in which the function of elderly organs has decreased so as to cause hypertension. The purpose of this study is to analyze the effect of melon juice on the decrease of hypertension in the elderly study at posyandu elderly village kemiri. This research design was one group pre test post test design, populationis all elderly who have hypertension in village of Ketegan amounted to 87 elderly and sample amounted to 30 elderly by total sampling method. The are 2 variables that is the independent variabel melon juice and dependent variable is the decrease of hypertension in elderly. Date collection using soup and blood pressure observation sheets before an after juice. Date processing techniques using editing, coding, scoring, ang tabulating. As well as his stastistic test using the Wilcoxon test. The pressure research results blood before juice given almost halt of respondentshave systole blood pressure 160-169 mmHg a number of 5 respondents (39%) and almost all respondents diastole blood pressure 90-100 mmHg a number of 12 respondents (92%). Blood pressure after being given melon juice for 7 days most of the respondents had blood pressure systole 131-140 mmHg of 7 respondents (54%) and al most all respondents had blood pressure diastole 70-80 mmHgof 12 respondents (92%), the Wilxocon test shows that the significant value of p = 0,000 < α (0,005), therefore rejected and accepted. The conclucion is there is the the effect of melon juice on the decrease of hypertension in the elderly study at posyandu elderly village Ketegan.